Lightning Impact on the Transmission Line and Its Mitigation using Matlab Simulink - Farid, Farhan; Dur Muhammad Soomro, (Evolution in Electrical and Electronic Engineering, 2022)
Transmission lines are a power system component (PS). Lightning strikes, for example, are a natural impact that transmission lines are constantly subjected to. Humans are powerless to stop the occurrence. Lightning strikes the PS, causing an impulsive transient and affecting the transmission line's equipment's power quality. The industrial sector might be a victim of this issue and suffer a considerable loss. Equally, as a solution to this problem, mitigating techniques may be used in the system to assure PS's long-term viability and high performance. In this paper, this project aims to simulate a surge arrestor in transmission lines to reduce the effect of lightning strikes. MOSA (Metal Oxide Surge Arrestor) is the mitigating technology employed in this project. MATLAB Simulink software was used to simulate the MOSA. The project's results include steady-state output waveforms, surge waveforms caused by lightning strikes, and mitigation results applying the suggested mitigation approach. To obtain the best result for this project, one recommendation for future work is to use different simulation tools like PSCAD to mitigate the lightning impact on the transmission line.